Resveratrol as a Novel Therapeutic Agent for Treating Duchenne Muscular Dystrophy - Burt, Matthew (Université d'Ottawa / University of Ottawa, 2013)
Duchenne Muscular Dystrophy (DMD) is an x-linked neuromuscular disease that is caused by an absence of dystrophin protein, rendering skeletal muscle more susceptible to contraction-induced damage. One therapeutic strategy focuses on increasing the expression of endogenous utrophin A, a dystrophin homologue. Interestingly, slow muscle is more resistant to the dystrophic pathology and has increased utrophin A expression (Webster 1998; Gramolini 2001b). These observations led researchers to explore the therapeutic potential of stimulating the slow, oxidative myogenic program (SOMP) in the mdx context. Beneficial adaptations were seen with pharmacological activation of PPARδ and AMPK. We treated mdx mice with resveratrol (~100mg/kg/day), a putative SIRT1 activator, for 6-7 weeks and evaluated the activity of phenotypic modifiers that are known to influence the SOMP. SIRT1 activity and protein levels increased significantly, as well as downstream PGC-1α activity. There was evidence of a fibre type conversion as the treated mice had a higher proportion of the slow myosin heavy chain isoforms in both the EDL and Soleus skeletal muscles. Utrophin A protein levels showed modest, but consistent increases with resveratrol treatment. Finally, histological analysis revealed improvements in central nucleation and fibre size variability. These findings were promising, but raised the question of whether modifying the treatment regimen may result in greater therapeutic benefits. Surprisingly, we discovered that an elevated dose of 500mg/kg/day was ineffective in its promotion of the SOMP. SIRT1 was not activated and there was no change in utrophin A levels with resveratrol treatment. Taken together, this study demonstrates that resveratrol has the ability to promote the SOMP through SIRT1 and PGC-1α activation. It also highlights the importance of selecting an appropriate dose of resveratrol to maximize its effectiveness.
Keywords: resveratrol; skeletal muscle; utrophin; dystrophin; mdx; duchenne muscular dystropy; slow oxidative myogenic program; sirt1; pgc-1 alpha